Pengembangan Perangkat Pembelajaran Fisika Berbasis Masalah Untuk Meningkatkan Kemampuan Berpikir Kritis - Siti Idiatul Hasanah; Susilawati Susilawati; Joni Rokhmat (Journal of Education, Science, Geology, and Geophysics (GeoScienceEdu), 2021)
This study aims to develop problem-based learning tools to improve critical thinking skills that are valid, efficient, and effective for use in learning on harmonious vibration material. This research is a type of research and development (R&D) with a 4D model. At the define stage, is the initial stage for defining the problem. The design stage, designing learning device products in the form of syllabus, lesson plans, student worksheet, critical thinking skills test instruments, and learning videos. The develop stage is the development of the device from the results of the validity of the learning tools obtained from the validation results of 6 validators consisting of 3 expert validators and 3 on validators. The practicality or efficiency of the learning device is obtained from the responses of students and the learning implementation sheet. Increased critical thinking ability of students to analyze by determining the standard acquisition of the results before and after learning. The results of the validation show that the learning device components are in the very valid category for the syllabus and valid enough for lesson plans, student worksheet, critical instrument test skills, and video learning which means that they are good enough to be used in learning Reliability of the syllabus, lesson plans, student worksheet, critical thinking ability test instruments, and learning videos above 75% show all components that are in the reliable category. The results of student responses, as well as the implementation of learning are in the very practical category. Student learning outcomes have increased with a acquisition value of 0.66 which is in the medium category. Based on these results, it can change valid, efficient and effective problem-based learning tools used to improve students' thinking skills. The last stage is to disseminate the dissemination stage of the device where at this stage it is done by making journals to send